The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1046/j.1528-1157.2001.080873.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Spectroscopy and Histopathological Findings in Temporal Lobe Epilepsy

Abstract: Summary:Purpose: In some patients with temporal lobe epilepsy, histopathological evaluation of resected brain tissue after surgical treatment may reveal several features indicative of discrete cortical malformations. We sought to determine whether these histopathological features were accompanied by hippocampal changes detectable preoperatively by proton magnetic resonance (MR) spectroscopy and to evaluate their relationship with postoperative outcome.Methods: In 25 consecutive temporal lobe epilepsy patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Contralateral spectroscopic alterations in MTLE may have a variety of causes, such as bilateral hippocampal sclerosis, widespread malformations of cortical development, non-specific damage of the hippocampus due to prolonged seizure activity, or its specific secondary damage due to preferential activation of the neural connections between hippocampi on both sides [11,23,33]. Our surgical series did not include any patient with bitemporal seizure origin, but contralateral spectroscopic abnormalities were noted in 89% of cases.…”
Section: H-mrs and Prediction Of Seizure Outcome After Surgery For mentioning
confidence: 96%
See 1 more Smart Citation
“…Contralateral spectroscopic alterations in MTLE may have a variety of causes, such as bilateral hippocampal sclerosis, widespread malformations of cortical development, non-specific damage of the hippocampus due to prolonged seizure activity, or its specific secondary damage due to preferential activation of the neural connections between hippocampi on both sides [11,23,33]. Our surgical series did not include any patient with bitemporal seizure origin, but contralateral spectroscopic abnormalities were noted in 89% of cases.…”
Section: H-mrs and Prediction Of Seizure Outcome After Surgery For mentioning
confidence: 96%
“…Several reports have suggested that 1 H-MRS-detected metabolic data might be useful for prediction of surgical outcome in patients with MTLE [13,15,16,23,24,26,28,29,31]. Two favorable factors for both postoperative reduction of seizure frequency and freedom from disabling seizures are usually mentioned: (1) significant asymmetry of the metabolic alterations with their predominance on the side of surgery and concordance with MRI and EEG data; and (2) the absence of the spectroscopic abnormalities in the contralateral temporal lobe.…”
Section: H-mrs and Prediction Of Seizure Outcome After Surgery For mentioning
confidence: 99%
“…Significantly more frequent bilateral 1 H MRS abnormalities in MTLE patients with histopathologically proven temporal pole MCD were reported [27], and the authors speculated about more widespread developmental changes in patients with cortical malformations that could be responsible for bilateral 1 H MRS changes as well as for worse surgical outcomes in this group of patients. In contrast, four of our six cases with bilateral 1 H MRS abnormalities had no MCD in their temporal poles.…”
Section: Discussionmentioning
confidence: 97%
“…Malformations of cortical development (MCD) have been repeatedly found in a significant proportion of MTLE cases, especially in children [22][23][24][25]. It has been suggested that different histopathological subgroups of MTLE may have different etiopathogeneses [23,26], but a relationship to 1 H MRS findings has been only rarely approached [27].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of PMRSI and MRI volumetry can accurately and non-invasively lateralize TLE in the majority of patients [17]. Stefan et al found that PMRS could detect subtle abnormalities that were not apparent on MRI [107]. Another study indicated that hippocampal structural damage may be depicted by PMRS [36].…”
Section: Partial Epilepsymentioning
confidence: 99%